ISOCHORIC PATHS IN IMMISCIBLE FLUIDS AND THE INTERPRETATION OF MULTICOMPONENT FLUID INCLUSIONS - Diamond L.W. (My University, 1996)
Fluid inclusions in minerals often follow isochoric-isoplethic paths through P-T space, both in nature and during microthermometry. The systematics which arise from this behaviour are the basis for interpreting fluid inclusion analyses. Previous studies have claimed that isochoric-isoplethic paths may transect a given phase boundary only once, and natural fluid inclusions have been interpreted accordingly. Herein it is demonstrated on theoretical and experimental grounds that such claims are false. Multicomponent fluid inclusions may indeed show the disappearance then reappearance of liquid or vapour phases during microthermometric heating, without violating the isochoric-isoplethic constraints. This result reinstates some formerly discredited observations of natural fluid inclusions; it requires modification of the way in which fluid inclusions are studied by microthermometry; and it opens new possibilities to understand the occurrence and geochemical effects of immiscibility at high temperature and pressure in the lithosphere.The following sequences of phase transitions are deduced to be feasible upon heating multicomponent fluid inclusions: (1) liq -> liq1 -> liq2 -> liq; (2) liq + vap (or liq2) -> liq -> liq + vap (or liq2); (3) liq + vap -> liq1 + liq2 + vap -> liq + vap; (4) liq + vap -> liq1 + liq2 + vap -> liq1 + liq2; (5) sol + liq + vap -> sol + liq -> sol + liq + vap; (6) liq1 + liq2 -> liq -> liq1 + liq2 -> liq. Only some of these sequences have been reported so far from natural inclusions. Presumably the remaining sequences have not been found because, following conventional wisdom, systematic observations have never been made at temperatures above the first total homogenisation transition. Investigators are therefore urged to conduct such measurements in the light of this new result and to make use of new technology to inhibit decrepitation.Fluid inclusions which display the above sequences cannot be interpreted in the same way as inclusions with only one intersection of an immiscibility boundary. If the assemblage of inclusions shows petrographic evidence for homogeneous trapping, there is no way to deduce from the inclusion measurements alone, on which segment of the isochore the inclusion was trapped. Conversely, if petrography indicates heterogeneous trapping, microthermometry does not yield a unique formation temperature. Rather, there may be up to three possible P-T points of entrapment.Based on the concept of global phase diagrams and on analogues with better known fluids, speculations are made on the topology of the CO2-H2O-NaCl and similar systems. It seems likely that the immiscibility field closes at high temperatures, thereby allowing the region of high-pressure, low-temperature liquid to join the vapour field at low pressures and high temperatures. Isochores in these systems may therefore exhibit type six behaviour listed above.